Financial Planning in Rig Vedic Literature: Some Evidences - Balakailasanathasarma, M.; Navaneethakrishnan, S. (University of Jaffna, 2021)
Interdisciplinary research studies explore ways to build bridges between subjects through their nature. Rig Vedic literature is one of the ancient Sanskrit literature consist of variety of concepts not only limited to religion but also other knowledge bases. Several research studies prove wide spectrums of modern theories are influenced by these concepts including management theories. In Vedic Hindu mythology, business is seen as a legitimate, integral part of society. This study made an attempt to highlight specific Rig Vedic texts that deal with financial management principles and planning for the better understanding about the Vedic concepts in relation to current financial planning concepts. Using mixed method including comparative and critical analytical methods, this study explains the identified elements of the financial planning in Rig Vedic literature. Findings of the study reveal that ancient Vedic literature reveals as rooting path to the current financial planning theories. They call attention to that treasure has to be earned only through fair means and one should put in his best efforts to acquire wealth through ethical and moral practices. They assert that there shall be proper distribution of wealth from the wealthy to the poor. They also condemn those who enjoy wealth without partaking it with others. They repeatedly call upon everyone to earn and maximize wealth and drive away poverty. This contribution is significant as it allows researchers who want to find out whether there might be influence of Rig veda on certain other management and leadership-functions in the Indian context but lack of research studies to be able to do so.
Keywords: Financial Management; Management; Rig veda; Sanskrit; Vedic Literature